Assistance in Making a Business Identification Number as a Business Legality for MSME Actors in Cibeusi Village, Subang District - Ciater - Ujang Charda S; Ajun Juana; Restu Mahardhika (PT FORMOSA CENDEKIA GLOBAL, 2022)
MSMEs are the economic support of the community. In Indonesia, MSMEs themselves have been defined in the Law of the Republic of Indonesia Number 20 of 2008 concerning MSMEs, which states micro-enterprises and productive businesses belong to individuals and/or individual business entities that have micro criteria as regulated in the Law. MSMEs are a strategic Indonesian economic sector for economic development in Indonesia. But in reality, MSMEs have problems and until now there has been no serious attention to overcome them. MSMEs need serious protection, especially from the free market. The protection in question is in strengthening human resources, coaching, housing, business environment, and promotion.